Providing learning support in the Malaysian context of open and distance learning (ODL) issues and concerns - Dzakiria, Hisham (Universiti Utara Malaysia, 2006)
This book of readings is about one specific but vital aspect of Open Distance Learning (ODL): Learning Support in Distance Education (DE).In many ways, learning support has not received the attention it fully deserves.There needs to be a strong emphasis on the provision of learner support, which is designed to facilitate learning and interaction between learners, the distance teachers and the content. Learner support is a very important component of distance education.Ensuring success of learners in distance learning settings requires more than access to technical and supplemental services.It requires that all stakeholders in DE be aware of the issues on providing optimal learning support.It also means that distance teachers, tutors and technical staff in adjunct service areas must be prepared for interaction with students who may be heterogeneous and not traditional in age or attitude toward learning. The target audience of this book is a wide range of staff either currently involved in ODL schemes or about to start. They may be distance teachers, tutors, advisers,counsellors working directly with distance learners or administrators and mangers organising learning support in DE.They may work in a variety of institutions, some purely operating at a distance, some in a mixed or dual mode institutions.The intention above all is to produce a practical resource of immediate use by Malaysian DE stakeholders